The Effect of Ambient Ageing on the Corrosion Protective Properties of a Lithium-Based Conversion Layer. Issue 3 (17th March 2023) - Li, Ziyu; Homborg, Axel; Gonzalez-Garcia, Yaiza; Visser, Peter; Soleimani, Mohammad; Mol, Arjan
Abstract : The influence of ageing under ambient conditions on the corrosion protective behaviour of a lithium-based conversion layer on AA2024-T3 is studied in this work. Conversion layers aged at ambient conditions for relatively short times (0 h and 4 h), show an initial high degree of corrosion inhibition but a much lower protectiveness after the inhibition stage terminates. Conversion layers with relatively long ageing times (24 h and 72 h) show a rather stable corrosion resistance which is higher than that of short-time aged samples. It is hypothesized that the freshly-formed conversion layer has trapped a certain amount of lithium ions and water molecules, leading to ongoing and heterogeneous growth of the conversion layer with time under ambient indoor conditions. Moreover, conversion layers with short ageing times show early-stage active corrosion protection by lithium-ion release.